Cryoprotection with Polyethylene Glycols and Dextrans During Freezing of Erythrocytes with Low Hematocrit - Ramazanov, V. V.; Bondarenko, V. A. (Problems of Cryobiology and Cryomedicine, 2007)
The effect of different concentrations of polymers on the survival of the erythrocytes frozen with low hematocrit (0.8%) was investigated. A significant reduction of cryoprotective activity was noted, as well as damaging effect of PEG-1500 under 20% concentration under conditions of ionic strength and increased sucrose concentration was revealed. A rise in hematocrit in the freezing medium up to 40% eliminates this effect. The presence of penetrating cryoprotectants in cryopreservative results is less manifested dependence of cryoprotection with PEG-1500 on ionic strength. The experiments on substitution of Na+ cation to NH4+ one when suing sucrose-salt medium with high concentration of sucrose enable the supposing that the balance of cryoprotective and damaging effect of polymers is determined by their molecular mass and depends on the intensity of augmentation of osmotic gradient on cell membrane during freezing.